2009
DOI: 10.1073/pnas.0813393106
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of tight junction ion selectivity in human airway epithelia

Abstract: Electrolyte transport through and between airway epithelial cells controls the quantity and composition of the overlying liquid. Many studies have shown acute regulation of transcellular ion transport in airway epithelia. However, whether ion transport through tight junctions can also be acutely regulated is poorly understood both in airway and other epithelia. To investigate the paracellular pathway, we used primary cultures of differentiated human airway epithelia and assessed expression of claudins, the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 43 publications
0
59
0
2
Order By: Relevance
“…H 1 receptors seem to play the most important role; in airway epithelia (Flynn et al 2009, Chan et al 1987, in vascular epithelia (Flynn et al 2009), in nostrils (Yang et al 2003), in Fallopian tubes and ovaries (Downing et al 1999(Downing et al , 2002 and in human colon (Keely et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…H 1 receptors seem to play the most important role; in airway epithelia (Flynn et al 2009, Chan et al 1987, in vascular epithelia (Flynn et al 2009), in nostrils (Yang et al 2003), in Fallopian tubes and ovaries (Downing et al 1999(Downing et al , 2002 and in human colon (Keely et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is considered to regulate ion transportation influencing mainly the paracellular pathway; it affects the tight junctions of adjacent cells and acutely increases the Na + conductance in airway epithelia (Flynn et al 2009, Hirace et al 2001, Zabner et al 2003. Conversely, histamine interferes with cellular transportation by regulating the ion transporters rather than altering the paracellular permeability and it increases electrical resistance of the human bronchial epithelial cells without increasing the permeability through the tight junctions, (Devalia et al 1994) an event which was also demonstrated in the porcine proximal colon cells (Ahrens et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations